Continuum damage mechanics based ductile fatigue-fracture prediction in buckling steel braces. (September 2021) - Zhu, Yazhi; Fell, Benjamin; Kanvinde, Amit
Abstract: A Continuum Damage Mechanics criterion (the Stress Weighted Ductile Fracture Model - SWDFM) is used to predict Ultra Low Cycle Fatigue fracture in buckling steel braces. The focus is to examine the efficacy of this approach for predicting fracture in large-scale structural components with localization, when the constitutive and fracture parameters have been calibrated only at the coupon scale. A dataset consisting of 11 two-thirds scale, cyclically loaded, hollow brace specimens, and corresponding material coupon specimens is utilized for assessment of the fracture prediction approach. In these tests, fracture occurs either at the center where cyclic local buckling amplifies the strains, or at the gusset-plate connections. Particle Swarm Optimization is used to calibrate material constitutive parameters based on load-deformation response of the coupon tests, whereas the SWDFM parameters are calibrated using their fracture response. These parameters are applied within Continuum Finite Element simulations of the brace tests. The results indicate that the approach predicts fracture in a satisfactory manner. The error in fracture predictions is most correlated with the error in predicting the event of localization (i.e., local buckling). There does not appear to be a strong relationship between the error in the constitutive model calibration (based on the coupon tests) and the prediction of either local buckling or fracture. This suggests that in themselves, the small-scale coupon specimens are unable to calibrate the constitutive model with the required accuracy to capture localization. Commentary is provided for calibration and application of the CDM-based approach to predict fracture. Graphical abstract: Unlabelled Image Highlights: A continuum damage mechanics criterion is applied to predict ultra low cycle fatigue in buckling steel braces. The efficacy of the approach is assessed against data from 11 two-thirds scale experiments. The approach predicts fracture in a satisfactory manner, but is dependent on the prediction of the event of localization, i.e., local buckling. Coupon tests appear inadequate to estimate constitutive parameters with the resolution needed to predict this localization.